Jenis Tumbuhan Paku di Kawasan Terutung Kute Kecamatan Darul Hasanah Kabupaten Aceh Tenggara - Nurdin Amin; Jumisah Jumisah (Universitas Islam Negeri Ar-Raniry, 2019)
A research is conducted to identify the types of ferns found in the Terutung Kute in Darul Hasanah District, Southeast Aceh. Method used in this study was an exploratory survey which was carried out with a 50 x 10 m transect that was spread throughout the area including mountains, plantations, settlements and watersheds. The study found 11 types of ferns from 8 families, namely Asplenium longissium, Asplenium tenerum, Diplazium accentens Blume, Davallia corniculata, Davallia trichomanoides, Orthioptheris sp, Lindsaea sp, Nephrolepis falcate, Heterogenium sp., Cyclosorus gongylodes and Cylosorus sp. The total number of individuals found in the Kute Terutung area are 131. The highest number of individuals is found in residential areas as much as 34, while in the mountainous regions are 32, watershed areas are 27. The least number of individuals is found in plantation areas as much as 22 individuals.